Tribute to Dodong Nemenzo, TWSC Founder - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 32 No 1,2 (2017): TWSC and Forty Years of Critical Scholarship, 2018)
Proceedings of the tribute to Francisco "Dodong" Nemenzo, founder of the UP Third World Studies Center, during the fortieth anniversary conference of the UP Third World Studies Center, 9-10 February 2017